Analisis wacana kritis dalam pembelajaran: Peran AWK pada pembelajaran literasi kritis, berpikir kritis, dan kesadaran berbahasa kritis - Sarasati, Ruruh (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2020)
Critical discourse analysis has been used to determine the power relations that occur in the process of production and reproduction of meaning. The structure of knowledge influences the course of the practice of disclosure. The intended knowledge is not only knowledge that is known by the speaker, but the knowledge of the listener or reader. This places critical discourse analysis in a multidisciplinary view. The multidisciplinary view is currently inherent in the analysis of critical discourse and raises the potential for the involvement of critical discourse analysis in the discourses that arise in the classroom. Furthermore, critical discourse analysis can also play a role in learning. This article conveys the potential role of Critical Discourse Analysis in critical literacy learning, critical thinking, and critical language awareness.